Study on Gtem-cell - Syarfa' Zahirah Sapuan (2010)
The most important electromagnetic compatibility for electrical devices is its capability to operate safely in an electromagnetic environment and will not produce or be susceptible to interference. The measurement method for radiated emission and radiated susceptibility requires a method, which is reliable and reproducible. This is important to ensure the measurement fulfill the electromagnetic compatibility (EMC) standard. The Gigahertz Transverse Electromagnetic Mode (GTEM) may be viewed as a careful combination of TEM cell (Crawford cell) and the anechoic chamber. Therefore, in order to fulfill the requirement of EMC, its need to be evaluated especially its electric field distributions. The aim of this project is to study the electric field distribution in the GTEM cell which is important for EMC calibration measurements. The electric field must have uniformity in the working volume of the cell. Therefore, a simple method for calculating electric fields in GTEM cell proposed by Kama Huang [1] is used in this project. This method based on the coordinated transformation and quasi static approximations and has provided the simulation evident by commercial software (FD-TD method-microwave studio) in comparison with this method. By changing the position of the septum closed to the upper conductor of the GTEM cell will not give a solution to expand the test region. Nevertheless, by folding at the point of 1/3 of septum height, the uniformity of the electric field changes as long as the angle of the modification not more than 45 degree. Both of the modification generated by commercial software (microwave studio).